An empirical ship domain based on evasive maneuver and perceived collision risk. (September 2021) - Du, Lei; Banda, Osiris A. Valdez; Huang, Yamin; Goerlandt, Floris; Kujala, Pentti; Zhang, Weibin
Highlights: A risk perception-based ship domain is proposed. This domain accounts for the timing of ship taking evasive maneuvering. The size of this domain is empirically determined over ship encounters in AIS data. Available maneuvering margin is employed as a proxy for risk perception. The size of the domain varies with ship size, ship length and COLREGs identity. Abstract: This paper introduced a new ship domain concept and an analytical framework. The ship domain takes the point of the ship's first evasive maneuver as a basis and correlates it with the navigator-perceived collision risk level. The first evasive maneuver of a ship is detected based on the ship turning point identification and ship intention estimation. The available maneuvering margin (AMM) is utilized as a proxy to measure the perceived collision risk by the navigator. Interpreting the first evasive maneuver in terms of this AMM over a large sample of vessel encounters taken from automatic identification system (AIS) data finally enables an empirical estimation of the size of this ship domain. The method is applied to AIS data in the Northern Baltic Sea, and separate ship domains are constructed for the give-way and stand-on vessels with different maneuverability characteristics. Compared to the existing proximity-based ship domain, this ship domain explicitly incorporates the dynamic nature of the encounter process and the navigator's evasive maneuvers. Several advantages of this proposed ship domain concept and limitations of the presented modeling approach are discussed. Finally, possible future applications are explained, including waterway safety assessment and navigational decision support systems to reduce ship-ship collision risk.